Phenomenal and virtual views on music related to buddhism in 21st-century Malaysia - Chow, Ow Wei (2015)
Music related to Buddhism, or Buddhist music in general, gains attention only in the recent decades. Mahāyāna Buddhism substantially registers the importance of music, despite a restriction on the monastic involvement in music performance. While Vajrayāna Buddhism and ‘engaged Buddhism’ have emerged as a global trend that increasingly applies a musical context in many religious movements, Buddhist music is rather deemed problematic to Theravādins. To gaze this music with a philosophical perspective, phenomenality is employed as one of the typical Buddhist emphasises that promotes a detachment from the delusion of worldly existence. In this context, music is merely reflected as a perceived phenomenon. The virtual perspective is another access point to the concept of phenomenality since the internet has created a new dimension that transcends the boundaries across time and space. Subsequently, music enthusiasts, knowledge seekers, and Buddhist practitioners in 21st-century Malaysia, who no longer need to overcome the problems of distance and unscheduled absence at a specific location, are allowed to access relevant data conveniently according to various needs. Malaysians embrace an innovatory ‘tech’ life that drastically transforms urban lifestyle with a newly developed ‘mobile-only’ culture in the 21st century, a time widely regarded as the digital era. However, the adaptation of a ‘tech’ lifestyle brings about a question of existence in virtuality, which is also connected to the online experience of Buddhist music. Spreading fast through a virtual platform, Buddhist music somehow appears in diverse styles but it also perpetuates a possibility for its musical attributes to remain questionable. This qualitative research explores possible connections of music related to Buddhism with parallel ideas of phenomenality and virtuality, and investigates the emphasis of the contexts of ‘Buddhism’ and ‘music’ as well as aspects that makes music ‘Buddhist’ by considering music seen from multiple perspectives. Employing a contemporary view of virtual ethnography by Hine, this musicology on Buddhist music in 21st-century Malaysia undertakes a combination of qualitative analytical methods in which discourse analysis, hermeneutic phenomenology, metaphorical analysis, ethnostatistics and music analysis significantly operate on data sources as a way of knowing. This study consciously regards all music related to Buddhism as an all-inclusive genre called ‘Buddhism-related music’, while the term ‘Buddhist music’, which is adopted to classify or describe this typical music, is employed interchangeably though both terms are not entirely the same in their specific contexts. As the outcomes, it is found out that Buddhism-related music hardly constitutes significant typological criteria based on its sonic and stylistic attributes. Though variously defined, this music can be identified simply through a conceptualised content that interpretatively represents an idea related to Buddhism. With the understanding of ‘emptiness’, a more universal view can be projected in the ethics of the making of Buddhist music. Virtuality as an integral part of reality affects the making of the object in parallel with the causation of phenomenality. Buddhist music can be considered as both a phenomenal and virtual being, therefore suggesting an insight to consider separable contexts of ‘Buddhism’ and ‘music’, as music is deemed secondary to the goal of Buddhist practice. The notion of ‘emptiness’ advocates an undertaking of the ‘middle path’ for composers, musicians and audiences to access Buddhist music. Finally, this leads the study to formulate an idea of the ‘Buddhist being’ in music.